Postmodern Aesthetics in Karawitan's Work "Menteng" | Estetika Postmodern dalam Karya Karawitan “Menteng” - Putu Budiartawan, Pande (GHURNITA: Jurnal Seni Karawitan, 2024)
"Menteng" is a work of musical art, the Final Project of the ISI Denpasar Musical Arts Study Program. This work is inspired by the process of making Selonding gamelan blades, which is called menteng (forging). The phrasing medium used in this work is the Selonding gamelan. This article aims to describe the stages of creation and form of the musical work "Menteng" and the postmodern aesthetic values contained therein. This research proposes the descriptive qualitative method. Through this approach, it is hoped that we can describe a comprehensive picture of the stages of creation, the structure of the work, and the elements of postmodern aesthetics contained in the musical work "Menteng." The results of this research show that the musical work "Menteng" uses the Panca Sthiti Nawi Sani creation stages, which consist of five stages: ngawirasa, ngawacak, ngaplan, ngawangun, and ngebah. This work has a three-part structure consisting of part 1, part 2, and part 3. In addition, the musical work "Menteng" contains postmodern aesthetic values such as pastiche, camp, and schizophrenia.